Conceptual Engineering of Plasma-Focus Thermonuclear Pulsors - Moreno, Cesar Hugo (2000)
A new method of significant efficiency enhancement, which is based on simultaneous interaction of electrons with an opposite wave at the second cyclotron harmonic, and a forward wave of the same frequency, at the fundamental cyclotron resonance, is proposed for the backward wave oscillator (gyro-BWO). Excitation of the forward wave results in significant efficiency enhancement, whereas the opposite wave provides a broadband feedback. This allows realizing a high-efficiency, frequency-tunable oscillator. Index Terms-Broadband gyro-oscillator, cyclotron resonance maser, gyro-BWO, gyro-TWT. )